Testing on Market Efficiency of the Cacao Commodity for the Futures Market in Jakarta Future Exchange - Ria Maulida; Lukytawati Anggraeni; Samsul Hidayat Pasaribu (School of Business, Bogor Agricultural University (SB-IPB), 2018)
The investigation of the efficient market validity hypothesis is a favorite topic in financial literature. However, there are still limited research on futures market commodity, especially the futures market in Indonesia. The objectives of this study were to analyze the development of cacao commodity futures market trading and determine its market efficiency. This study used value of trading volume, daily spot price and futures price of cacao commodity trading market from December 2011 to December 2016. Descriptive analysis showed that the development of cacao commodity futures trading market from value of trading volume of cacao commodity experienced fluctuating growth between -126.050% and 39.480%, and average growth of cacao by -6.462%. Augmented Dickey-Fuller (ADF) root test, Augmented Engle Granger (AEG) Error Correction Model Test (ECM) were used as the bases for the analyses. The results of the study showed that cocoa commodity futures market in Indonesia is an efficient market and contained risk premium. The implication of this research for market participants or investors is that they may choose to carry out hedging activities because cacao is an efficient market in the short term and contains risk premium.